A performatividade do fio e da linha nas aulas de artes visuais - Silva, Marcia Inez da (2023)
This research is a reflection on the performativity of the "thread and the line" in the teaching of the Visual Arts and intends to raise the debate about art as a field of research and teaching experience. The justification for the work lies in the relevance of reflecting on the teaching-learning process of the curricular component Art, in the early years of elementary school, by teachers without specific training based on the aesthetic codes of erudite art, which may imply vague conception of art and even lack of repertoire. Thus, the research is guided by the general objective: to reflect on the performativities of yarn and line in the teaching of Visual Arts, through workshops taught by me, using these materials with children from the early years of elementary school, experiencing the acts of embroidery, crochet, sew, weave and patch. In addition, I point out that it also aims to map artists and traditional textile collectives from Brazil and Latin America, investigating textile art in the production of intercultural audiovisual narratives through workshops, talking about performances, emotions and memories with the thread and the line in their daily lives, in a decolonial and transgressive perspective. In this sense, the research problem is the questioning about how my teaching practice, as regent, in the early years of elementary school, in the teaching of arts, can be transformative, not mechanical, based on dialogue, with a significant aesthetic experience, from the visualities present in the daily lives of students. Thus, when investigating performativities with yarn and line, I discuss the symbolic representations about the stories and affections of subjects who, using needles and cloths, produce scenes and plots, with hybrid creative processes that unite performance, interventions and technologies in the criticism of gender, aesthetic, ethnic-racial and social issues, as references for an art teaching. I also reflect on the importance and challenge of teacher training to promote a transgressive visual arts education with ample possibilities to teach the various aesthetic codes from a decolonial perspective, in plurality, for self-knowledge and social transformation. The research methodologies used were: field research with collectives and textile artists; action research with children aged 8 to 11 years at the Olegário Moreira Borges Municipal School (Goiânia), in ten workshops in the teaching of visual arts, involving TICS with the production of photographs and videos in the process of teaching and learning. Faced with the emergence of social isolation, which occurred due to the COVID-19 pandemic, the workshops were conducted in a hybrid way, in a mix between face-to-face and remote, which also generated reflections on teaching. As a result of the workshops in the teaching of visual arts, it was possible to experiment with threads and lines and reflect on the various developments caused by intercultural dialogues, based on the aesthetics of everyday life, permeated by digital technologies; and it was also possible to see that the textile poetics of artists and collectives of Latin American production brought to light problematizing questions about gender, ethnic-racial relations, identity and belonging, enabling literacies, image interpretations, writings and debates about the lived world. Thus, this research addresses art as experience, touching the lives of students and teacher, providing us the learning that thought and actions provoke reactions; and these, if thought and reflected, generate transformations, enable us to act differently, changing our lives and that of others. Finally, the lesson remains: learning to teach to look and think is to promote transgression and change through education.